Effects of the addition of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) on mechanical properties of luting and lining glass ionomer cement. (22nd July 2016) - Heravi, Farzin; Bagheri, Hossein; Rangrazi, Abdolrasoul; Zebarjad, Seyed Mojtaba
Abstract: Recently, the addition of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) into glass ionomer cements (GICs) has attracted interest due to its remineralization of teeth and its antibacterial effects. However, it should be investigated to ensure that the incorporation of CPP-ACP does not have significant adverse effects on its mechanical properties. The purpose of this study was to evaluate the effects of the addition of CPP-ACP on the mechanical properties of luting and lining GIC. The first step was to synthesize the CPP-ACP. Then the CPP-ACP at concentrations of 1%, 1.56% and 2% of CPP-ACP was added into a luting and lining GIC. GIC without CPP-ACP was used as a control group. The results revealed that the incorporation of CPP-ACP up to 1.56%(w/w) increased the flexural strength (29%), diametral tensile strength (36%) and microhardness (18%), followed by a reduction in these mechanical properties at 2%(w/w) CPP-ACP. The wear rate was significantly decreased (23%) in 1.56%(w/w) concentration of CPP-ACP and it was increased in 2%(w/w). Accordingly, the addition of 1.56%(w/w) CPP-ACP into luting and lining GIC had no adverse effect on the mechanical properties of luting and lining GIC and could be used in clinical practice.